2023
DOI: 10.3390/nu15153379
|View full text |Cite
|
Sign up to set email alerts
|

A Menthol-Enhanced “Cooling” Energy Gel Does Not Influence Laboratory Time Trial Performance in Trained Runners

Roxanne M. Vogel,
Nicole Varone,
Cayla Clark
et al.

Abstract: l-menthol (menthol) is an organic compound derived from peppermint which imparts a refreshing mint flavor and aroma to oral hygiene products, chewing gum, and topical analgesics. Menthol has been identified as a non-thermal sensory cooling strategy for athletes when ingested or mouth-rinsed during exercise in hot environments. Therefore, sports nutrition products delivering a controlled concentration of menthol could be beneficial for athletes exercising in the heat. We sought to test the performance and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In contrast, Vogel et al [24] reported that the menthol effect was negligible or trivial for the total distance covered during the 20 min time trial running performance measure in the menthol-enhanced energy gel condition (Cohen's d = 0.0). No significant differences emerged, and the menthol gel was inferior to a placebo gel.…”
Section: Mint and Menthol Gelmentioning
confidence: 88%
See 4 more Smart Citations
“…In contrast, Vogel et al [24] reported that the menthol effect was negligible or trivial for the total distance covered during the 20 min time trial running performance measure in the menthol-enhanced energy gel condition (Cohen's d = 0.0). No significant differences emerged, and the menthol gel was inferior to a placebo gel.…”
Section: Mint and Menthol Gelmentioning
confidence: 88%
“…Most studies used a within-participant design, except for three employing betweenparticipants [21,28,34]. Fifteen studies examined the placebo and nocebo effects of nutritional ergogenic aids [18][19][20][21]23,24,[26][27][28][29]31,[33][34][35][36]. At the same time, four focused on mechanical ergogenic aids [22,25,30,37], and one study investigated the open-label placebo [32] (see Table 3).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 3 more Smart Citations